y-6+2(4y+2)=-5(y+4)

Simple and best practice solution for y-6+2(4y+2)=-5(y+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-6+2(4y+2)=-5(y+4) equation:


Simplifying
y + -6 + 2(4y + 2) = -5(y + 4)

Reorder the terms:
y + -6 + 2(2 + 4y) = -5(y + 4)
y + -6 + (2 * 2 + 4y * 2) = -5(y + 4)
y + -6 + (4 + 8y) = -5(y + 4)

Reorder the terms:
-6 + 4 + y + 8y = -5(y + 4)

Combine like terms: -6 + 4 = -2
-2 + y + 8y = -5(y + 4)

Combine like terms: y + 8y = 9y
-2 + 9y = -5(y + 4)

Reorder the terms:
-2 + 9y = -5(4 + y)
-2 + 9y = (4 * -5 + y * -5)
-2 + 9y = (-20 + -5y)

Solving
-2 + 9y = -20 + -5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5y' to each side of the equation.
-2 + 9y + 5y = -20 + -5y + 5y

Combine like terms: 9y + 5y = 14y
-2 + 14y = -20 + -5y + 5y

Combine like terms: -5y + 5y = 0
-2 + 14y = -20 + 0
-2 + 14y = -20

Add '2' to each side of the equation.
-2 + 2 + 14y = -20 + 2

Combine like terms: -2 + 2 = 0
0 + 14y = -20 + 2
14y = -20 + 2

Combine like terms: -20 + 2 = -18
14y = -18

Divide each side by '14'.
y = -1.285714286

Simplifying
y = -1.285714286

See similar equations:

| 1.15z=61410 | | x+(x+1)+(x+2)+(x+3)+(x+4)+(x+5)=185 | | 12y=-96+8x | | 4(3a+4)-8= | | 4(4x-3)-6=12z-12-2x | | 60-5x=70-25x | | x(x-6)=14 | | -8x+2=8-6x | | -5(-3w+4)-7w=2(w-9)-5 | | (p^3-4p^2+p)-(3p^2+2p+7)=0 | | 4(a-8)=12a-6 | | 10x-4(x-6)=5x+5 | | 1v+7=13+4v | | -4(5x-6)+2=-20x+26 | | x^3y^4-y^4=0 | | (x+5)(-6)=0 | | -3+d=21 | | 2(v-2)=6v+7-3(-4v-1) | | [2x-4]=9 | | 7x+10=-2x+28 | | 1-1x=-1+1x-5-3 | | 7x+12x=-7-13 | | V=x^2h | | -4=-5v-9 | | 1.75x+2(.375x+4.5)=28.625 | | (-6.4x+6)(-6)= | | -4=(-4m+9m)-13 | | 4h+2=7h-19 | | x^2+y^2+2x-34=0 | | 5t+25-5= | | 3=5k | | X+2z= |

Equations solver categories